1979
DOI: 10.1207/s15328023top0604_3
|View full text |Cite
|
Sign up to set email alerts
|

Logical versus Empirical Estimates of Readability and Human Interest of General Psychology Textbooks

Abstract: As a contribution to the text selection task, 61 books were examined by the Flesch formulae and by student ratings to estimate validity and reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Introductory textbook readability studies that were more common in the 1970s and 1980s (e.g., Quereshi & Buchkoski, 1979) showed similar findings. Although readability programs (e.g., Flesch formulas) were definitely controversial, the findings of the readability studies, like Griggs's(1999) results for difficulty level, indicated substantial variability across texts.…”
Section: Level Of Difficultymentioning
confidence: 64%
“…Introductory textbook readability studies that were more common in the 1970s and 1980s (e.g., Quereshi & Buchkoski, 1979) showed similar findings. Although readability programs (e.g., Flesch formulas) were definitely controversial, the findings of the readability studies, like Griggs's(1999) results for difficulty level, indicated substantial variability across texts.…”
Section: Level Of Difficultymentioning
confidence: 64%
“…The content analysis approach pursued by him opened up the field of introductory textbooks to psychologists applying their usual methods of research. Quereshi and his various associates published four articles from 1975 to 1981 on content analysis and its various applications to textbooks (Quereshi & Zulli, ; Quereshi & Sackett ; Quereshi & Buchkoski, ; Quereshi, ) that were caught into our citation network as highly cited.…”
Section: Description Of a Constituency—quereshi In The 1970s And The mentioning
confidence: 99%
“…Huggins and Adams (1980, p. 91) claim that the "main weakness is that the difficulty of a passage involves its comprehension, and surface structure descriptions capture only some of the syntactic variables necessary to comprehension." Quereshi and Buchkoski (1979) had students rate reading ease based on two randomly selected paragraphs from each of 61 introductory psychology textbooks. They reported significant, but lower-than-expected correspondence between these subjective ratings and Flesch scores.…”
mentioning
confidence: 99%